Predictor factor for collective leadership: a case of secondary schools - Sivalingam, Shiveh; Abdul Kadir, Suhaida; Vejaratnam, Navaratnam; Asimiran, Soaib (Human Resource Management Academic Research Society, 2018)
The purpose of this paper was to study the factors predicting collective leadership in Malaysian secondary schools in Kuala Lumpur. The survey method is used to measure the variables, which influences collective leadership practices among 402 respondents from 103 government secondary schools in Kuala Lumpur. The findings utilized the inferential analysis – regression. The results show that school culture and sources of leadership efficacy are predictors for collective leadership. This Study focused on teachers from secondary government schools therefore results of this study cannot be projected liberally. The findings of the study supports the social exchange theory, which explains the relationship between the variables, studied. In addition, the findings of the research collaborate with Bandura’s (1986) theory with leadership elements. This paper introduces a new paradigm in research into sources of leadership efficacy and the concept of collective leadership.